Hands-Tied Hiring: How the EEOC’s Individualized Assessment is Taking Discretion Away From Employers’ Use of Criminal Background Checks - Valdez, Carrie (2015)
This article argues that the 2012 EEOC Guidance should not be given deference by the courts. Specifically, the Guidance’s individualized assessment, which imposes a heightened requirement on employers to justify their background check policies, is problematic in three important ways. First, the individualized assessment places an impractical burden by what it requires and whom it requires to conduct such an assessment. Second, employer liability for negligent hiring may actually increase if employers perform individualized assessments. Finally, the practical effect of the individualized assessment may be decreased employer reliance on criminal background checks, and the result will likely not be a better hiring outcome for minority applicants. Part II of this article provides a background of the disparate impact theory of discrimination and the defense of business necessity, surveys employers’ use of criminal background checks, explains the theory of negligent hiring, discusses the EEOC, the individualized assessment, and the EEOC’s initiative to aggressively regulate employers’ use of background checks, and examines recent cases litigating this issue. Part III analyzes the impractical burden the EEOC’s individualized assessment places on employers, argues that enforcement of the individualized assessment may increase employer liability for negligent hiring, and explores the contention that fewer minorities will, in fact, be hired if fewer employers rely on criminal background checks in making their hiring decisions. Part IV offers a solution that aims to satisfy the EEOC’s goal of eliminating the adverse impact of criminal background checks on blacks and Hispanics while simultaneously avoiding the impracticalities, inconsistencies, and other problems of the new Guidance